HUBUNGAN ANTARA WORKPLACE WELL-BEING DENGAN TURNOVER INTENTION PADA KARYAWAN PRODUKSI PT X BATAM - Gukguk, Yenni Br Raja; Anggraeni, Dewi Soerna (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Labor is a superior resource that can increase the productivity and sustainability of the company. In manufacturing companies, production activities are inseparable from labor in running them. Production activities in a company are considered as the heart of the company concerned. As the number of companies that emerge results in higher competition and the existence of employees becomes very important, but it turns out that there are workers who have the desire to leave the company, known as turnover intention. One of the factors that influence turnover intention is workplace well-being. This study aims to determine the relationship between workplace well-being and turnover intention in production employees of PT X Batam. The hypothesis in this study is that there is a negative relationship between workplace well-being and turnover intention in production employees of PT X Batam. The subjects of this study amounted to 92 production employees at PT X Batam. Data collection methods using turnover intention scale and workplace well-being scale. Data analysis technique using Pearson Product Moment correlation technique from Karl Pearson with SPSS version 27 for windows program. Based on the results of data analysis, the correlation coefficient (???) = -0.551 (p<0.050), meaning that there is a negative relationship between workplace well-being and turnover intention in production employees of PT X Batam. It is important for companies to improve employee well-being, through identifying problems early, evaluating and taking appropriate corrective actions to strengthen attachment to the company so as to minimize turnover intention in employees. Keyword: Workplace well-being, Turnover intention, Production employees Abstrak: Tenaga kerja merupakan sumber daya unggul yang dapat meningkatkan produktivitas dan keberlanjutan perusahaan. Pada perusahaan manufaktur, aktivitas produksi tidak terlepas dari tenaga kerja dalam menjalankannya. Kegiatan produksi di dalam suatu perusahaan dianggap  sebagai jantungnya perusahaan yang bersangkutan. Seiring banyaknya perusahaan yang muncul mengakibatkan semakin tingginya  persaingan ketat dan keberadaan karyawan menjadi sangat penting, namun ternyata terdapat tenaga kerja yang memiliki keinginan untuk meninggalkan perusahaan yang dikenal dengan turnover intention. Salah satu faktor yang mempengaruhi turnover intention adalah workplace well-being. Penelitian ini bertujuan untuk mengetahui hubungan antara workplace well-being dengan turnover intention pada karyawan produksi PT X Batam. Hipotesis dalam penelitian ini adalah terdapat hubungan negatif antara workplace well-being dengan turnover intention pada karyawan produksi PT X Batam. Subjek penelitian ini berjumlah 92 karyawan produksi di PT X Batam. Metode pengumpulan data menggunakan skala turnover intention dan skala workplace well-being. Teknik analisis data menggunakan teknik korelasi Pearson Product Moment dari Karl Pearson dengan program SPSS versi 27 for windows. Berdasarkan hasil analisis data diperoleh koefisien korelasi (???) = -0,551 (p<0.050), berarti terdapat hubungan negatif antara workplace well-being dengan turnover intention pada karyawan produksi PT X Batam. Penting bagi perusahaan meningkatkan kesejahteraan karyawan, melaui pengidentifikasian masalah sejak dini, evaluasi dan mengambil tindakan perbaikan yang tepat untuk memperkuat keterikatan pada perusahaan sehingga meminimalisir turnover intention pada karyawan. Kata kunci: Workplace well-being, Turnover intention, Karyawan produksi